Religion in Public Spaces in Contemporary Southeast Asia - Afrianty, Dina (Studia Islamika, 2012)
Religion is among the most overlooked factors in the development of nation-states in Southeast Asia. Some reasons for this include a bias emphasizing religious ideology in the study of anti-colonial organizations that dates to the origins of the politics of state formation; the influence of many ideas on the patterns of modern elite formations that stress the need for religion to shape national constitutions, and the fact that religion is difficult to neglect in shaping the behavior of masses in the region. Nevertheless, an early observation to the behavior of nations in Southeast Asia holds that religion influences the politics in public space varies from one country to another.DOI:Â 10.15408/sdi.v19i2.367Â